UNIVERSITIES' «THIRD MISSION* - A NEW VECTOR OF DEVELOPMENT? - Tatyana A. Balmasova (Высшее образование в России, 2016)
The article is devoted to «third mission» of universities. Having analyzed the practices of implementation of the «third mission », the author comes to a conclusion that complete copying and integrating of foreign ideas into the Russian higher education field is impossible without taking into account cultural diversity. In her research the author finds out that the change in mission of higher education, transformation of society into the «knowledge society» and market oriented modernization of domestic education reveal the necessity of seeking for an optimal way of its further development. In author's view, it is the public mission that may facilitate university, traditionally generating common benefit, to withstand the market without losing its identity and functions as a social institution.